Bianchi type III and Kantowski-Sachs cosmological models in Lyra geometry - Singh T.; Singh G.P. (My University, 2025)
Cosmological models for Bianchi type III and Kantowski-Sachs space-times within the framework of Lyra geometry are obtained. The physical behavior of the models is also discussed. © 1992 Plenum Publishing Corporation.